2013
DOI: 10.4103/0019-5413.108912
|View full text |Cite
|
Sign up to set email alerts
|

Four quadrant parallel peripheral screw fixation for displaced femoral neck fractures in elderly patients

Abstract: Background:The treatment options for displaced femoral neck fracture in elderly are screw fixation, hemiarthroplasty and total hip arthroplasty based primarily on age of the patient. The issues in screw fixation are ideal patient selection, optimal number of screws, optimal screw configuration and positioning inside the head and neck of femur. The problems of screw fixation may be loss of fixation, joint penetration, avascular necrosis of femoral head, nonunion, prolonged rehabilitation period and the need for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 22 publications
0
26
0
Order By: Relevance
“…Only 20 “saw bone” femora were tested. With 64 patients of FNF completing 2 years of followup in our study2 and performing the same in more than 200 cases in the past 6 years without any subtrochanteric fracture, we justify FQPP screw fixation pattern.
Figure 2A line diagram showing screw head positions at the entry site for different configurations. The first picture shows horizontal configuration of three screws in cadaver settings (note the closeness of the screws; they are almost in horizontal line).
…”
mentioning
confidence: 80%
See 3 more Smart Citations
“…Only 20 “saw bone” femora were tested. With 64 patients of FNF completing 2 years of followup in our study2 and performing the same in more than 200 cases in the past 6 years without any subtrochanteric fracture, we justify FQPP screw fixation pattern.
Figure 2A line diagram showing screw head positions at the entry site for different configurations. The first picture shows horizontal configuration of three screws in cadaver settings (note the closeness of the screws; they are almost in horizontal line).
…”
mentioning
confidence: 80%
“…Only 20 “saw bone” femora were tested. With 64 patients of FNF completing 2 years of followup in our study2 and performing the same in more than 200 cases in the past 6 years without any subtrochanteric fracture, we justify FQPP screw fixation pattern.…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…9,10 Sathish et al 11 concluded that by adding the fourth screw and keeping the screws in peripheral portion of the head and neck, the area of fixation can be easily increased in FNFs fixation.…”
mentioning
confidence: 99%